WIN-WIN SOLUTION DAN PRODUKTIVITAS ORGANISASI - Arrum Intan Sari; Nuraini Nuraini; Syifa Fauziah; Salfen Hasri; Sohiron Sohiron (Idaarah: Jurnal Manajemen Pendidikan, 2023)
This study aims to analyze and examine: win-win solutions and organizational productivity. This research is library research or library research. The data collection technique used is to find sources of reading both from books, articles, theses, dissertations and research reports. The data that has been obtained is then analyzed using content analysis. The result of this study is that conflict can be positive or negative depending on how it is resolved. One way that can process and overcome my conflict becomes positive or negative based on how to resolve it, both in terms of technique and strategy. Win-win solution is a strategy that can be applied and used in conflict resolution within the organization so that organizational productivity is disrupted or decreased. The main purpose of a win-win strategy is to fix the problem, not to hurt one party. The use of this strategy is to hear each other's input from various perspectives, define basic issues and create an atmosphere of mutual trust between all involved. In all of these strategies the problem is solved for the common good, not the private interest. The result of this strategy is a solution for those involved in conflict because a win-win solution meets individual needs, common interests and strengthens the relationship of all parties. Win win solutions can work efficiently if all parties work together to resolve conflicts that exist in the midst of the organization.